The Tomb of Teungku Di Anjong: From History, Art Artifacts and Revitalization Motive for the Development of Aceh Creative Batik Design - Herwandi, Herwandi; Ibrahim, Husaini; Yusdi, Muhammad (History Department, Semarang State University and Historian Society of Indonesia, 2019)
Teungku Di Anjong is a great ‘pries’ who lived during his reign of Sultan Alaudin Mahmud Shah in the kingdom of Aceh Darussalam (1760 - 1781 AD). He is buried in Gampong Peulanggahan, Kutaraja Sub-district, Banda Aceh City. His tomb is in an old mosque complex, which the people named by the Teungku Di Anjong Mosque. The tomb of Teungku Di Anjong along with his wife's grave named Syarifah, which is in a construct (cungkub), has a jirat and two beautifully decorated tombstones. The decorations are generally in harmony with Islamic art, filled with Arabic flower and calligraphic ornaments. Teungku Di Anjong Tomb is an art artifact, an art product of the creative industry in the 18th century ago in Aceh, which is a continuation of the tradition of decorating the tomb from earlier times. This article will discuss the history of Teungku Di Anjong, in dynamics and its role in the development of history in the kingdom of Aceh Darussalam. Then, it will see the artifacts of the tomb of Tengku Di Anjong, which is associated with the revitalization of the ornament on the tomb, which can produce a new patented